Tantangan Resolusi Konflik dalam Upaya Mewujudkan Perdamaian di Suriah - Sabiruddin, Sabiruddin (Universitas Al-azhar Indonesia, 2024)
The conflict in Syria has been going on for more than a decade, and is inflicting significant damage on the Middle East region. The complexity of the conflict in Syria is partly due to the involvement of regional and global powers. In this context, global peace efforts are an important focus for dealing with the conflict. This study aims to analyze the interests in the conflict in Syria and global peace efforts in dealing with it. This research was conducted using exploratory qualitative research methods. The theory used in this study is the theory of conflict resolution and peace in international relations. The research findings show that although efforts to achieve global peace continue, a complex set of challenges on the ground as well as prolonged geopolitical tensions continue to be major obstacles in the search for a peaceful solution for Syria.